Raven Hummingbird Paddle - Antoine, Kobe, (1999- ) (Artist) (2018)
Red cedar paddle with copper insert. Design in red and black acrylic paint. FDSNCA Graduate 2018. Lake Babine Nation. Copyright held by artist. Photograph by Highlight Studio.